2018
DOI: 10.5455/msm.2018.30.118-120
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence, the Fetal and Maternal Outcomes in Grand Multiparas Women

Abstract: Introduction:The incidence of grand multiparty in Saudi Arabia is high; there are no adequate studies about the grand multiparty.Aim:The aim to determine the prevalence, fetal and maternal outcomes in grand multipara women in comparison to primipara’s women.Methods:A retrospective study, the data was collected from our hospital records of labour and delivery unit started from January 2016 to December 2016.Results:The analysis was done in 415 charts divided into two group 1 consist of (120 primigravidas) used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
5
14
1
Order By: Relevance
“…Thirty-four cohort studies (42.0%) were identified as a prospective design (19 in [81], and three in the UAE). Fiftytwo (64.2%) cohort studies enrolled pregnant mothers at varying stages of their pregnancy with different characteristics such as diabetic and non-diabetic mothers [26,67], obesity [42,47,54], singleton [41,48,99] or triplet pregnancies [91], teenage women [112], multipara women [82,86,98], and women with systemic lupus erythematosus (SLE) [27]. Eight studies (9.9%) enrolled pregnant mothers at varying stages after delivery [24,49,58,59,81,84,88,99].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-four cohort studies (42.0%) were identified as a prospective design (19 in [81], and three in the UAE). Fiftytwo (64.2%) cohort studies enrolled pregnant mothers at varying stages of their pregnancy with different characteristics such as diabetic and non-diabetic mothers [26,67], obesity [42,47,54], singleton [41,48,99] or triplet pregnancies [91], teenage women [112], multipara women [82,86,98], and women with systemic lupus erythematosus (SLE) [27]. Eight studies (9.9%) enrolled pregnant mothers at varying stages after delivery [24,49,58,59,81,84,88,99].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Pre-GDM was also independently associated with CS delivery (adjusted odds ratio "aOR," 1.65), induction of labor (aOR, 1.67), macrosomia (aOR, 1.40), stillbirth (aOR, 3.66), and APGAR score < 7 at 5 min (aOR, 3.82) [67]. Various unfavorable health outcomes were more common in grand multipara compared to primigravida mothers [82,114] (see Additional file 3: Table S2). [26].…”
Section: Maternal or Reproductive Exposuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of these studies were mixed. Some studies concluded that grand multiparity is a great risk for many fetal and maternal complications including abnormal placentation, abruption placenta, malpresentation, and interventional delivery, and postpartum hemorrhage, prematurity, and neonatal and maternal admission to intensive care unit admission (6, 7).…”
Section: Introductionmentioning
confidence: 99%
“…Grand multiparity and a scarred uterus are known to increase fetal and neonatal morbidities [[24]]] [41],– [43]] but in this study, we didn’t find any statistically significant increased risk of fetal distress and neonatal morbidity between grand multiparous with or without scar (Table 4, Table 6). Fetal distress in the absence of uterine rupture might be related to grand multiparity rather than the scarred uterus status.…”
Section: Discussionmentioning
confidence: 55%